UPAYA PENANGGULANGAN TINDAK PIDANA PENCUCIAN UANG MELALUI PROVIDER CRYPTOCURRENCY ILEGAL di INDONESIA - NIM. A1011221163, MARIO CHRISTY SITUMORANG (Jurnal Fatwa Hukum, 2025)
Abstract The rapid development of crypto assets (cryptocurrencies) in Indonesia not only offers alternative investment instruments but also creates opportunities for their misuse as a means of money laundering, particularly at the layering stage. The anonymous, decentralized, and cross-border nature of crypto assets poses significant challenges for law enforcement authorities in terms of detection and enforcement. Moreover, the existing legal framework governing cryptocurrencies in Indonesia remains limited and does not specifically regulate mechanisms for preventing and combating money laundering conducted through illegal cryptocurrency service providers. This study employs normative legal research with statutory and conceptual approaches, aiming to analyze efforts to combat money laundering offenses carried out through illegal cryptocurrency providers in Indonesia. The findings indicate that Law Number 8 of 2010 on the Prevention and Eradication of Money Laundering Crimes can, in principle, address such offenses; however, its implementation remains ineffective. The main obstacles include limited technical capacity and human resources of law enforcement agencies in tracing complex cryptocurrency transactions, the proliferation of illegal crypto asset providers that fail to implement Anti-Money Laundering and Counter-Terrorism Financing (AML/CFT) principles, as well as inadequate inter-agency coordination and international cooperation in cross-border asset tracing. Therefore, comprehensive countermeasures are required, including the strengthening of specific regulatory frameworks, enhancement of digital investigative capacities, reinforcement of inter-agency synergy, and public education to increase legal awareness regarding the risks associated with the use of crypto assets. Kata kunci: Pencucian Uang, Cryptocurrency, Ilegal, Penanggulangan Abstrak Perkembangan aset kripto (cryptocurrency) di Indonesia tidak hanya menghadirkan alternatif instrumen investasi, tetapi juga berpotensi dimanfaatkan sebagai sarana tindak pidana pencucian uang, khususnya pada tahap layering. Karakteristik aset kripto yang bersifat anonim, terdesentralisasi, dan lintas batas menimbulkan tantangan serius bagi aparat penegak hukum dalam melakukan deteksi dan penindakan. Di sisi lain, pengaturan hukum mengenai aset kripto di Indonesia masih terbatas dan belum secara spesifik mengatur mekanisme penanggulangan tindak pidana pencucian uang yang dilakukan melalui penyedia layanan kripto ilegal. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual yang bertujuan untuk menganalisis upaya penanggulangan tindak pidana pencucian uang melalui provider cryptocurrency ilegal di Indonesia. Hasil penelitian menunjukkan bahwa Undang-Undang Nomor 8 Tahun 2010 tentang Pencegahan dan Pemberantasan Tindak Pidana Pencucian Uang secara normatif dapat menjangkau kejahatan tersebut, namun implementasinya belum optimal. Hambatan utama meliputi keterbatasan kapasitas teknis dan sumber daya manusia aparat penegak hukum dalam pelacakan transaksi kripto, maraknya penyelenggara aset kripto ilegal yang tidak menerapkan prinsip Anti Pencucian Uang dan Pencegahan Pendanaan Terorisme (APU-PPT), serta lemahnya koordinasi antarlembaga dan kerja sama internasional dalam penelusuran aset lintas yurisdiksi. Oleh karena itu, diperlukan upaya penanggulangan yang komprehensif melalui penguatan regulasi khusus, peningkatan kapasitas investigasi digital, penguatan sinergi antarlembaga, serta edukasi masyarakat guna meningkatkan kesadaran hukum dalam penggunaan aset kripto. Kata kunci: Money Laundering, Cryptocurrency, Illegal, Countermeasures